Rethinking decline of hegemony: a historical comparison between British and American financialization - Tursun, Özgün (2020)
The main purpose of this thesis is to analyse the relationship between financialization and the decline of hegemonic powers. While dominant views in the literature suggest that financialization leads to the decline of hegemonic powers based on historical comparison of the British hegemony between 1870-1890 and American hegemony between 1970-1990, this research argues these two cases are both conceptually and qualitatively different. There are three main shortcomings of the literature. First, they offer state-centric explanations of the decline of hegemonic powers. Second, they separate economics and politics. And finally, the role of ideology is overlooked. Conceptualizing financialization from a neo-Gramscian theoretical framework and rethinking the decline of hegemonic powers through this framework offers a holistic understanding of the congruence between financialization and the decline of hegemonic powers. The main argument of this thesis is that class struggle causes financialization which causes the decline of the hegemonic historical bloc but only if financialization occurs as an outward movement. In this respect, this research offers a fresh conceptualization of financialization as outward and inward financialization. The outward financialization that British hegemony has experienced result in the decline of the hegemonic historical bloc, the inward financialization of the American hegemony during the 1970s resulted in the reconfiguration of social forces in the US and the expansion of neoliberal social relations of production under the aegis of American hegemony. Overall, this research focuses on the period of 1870-1890 and 1970-1990 with a specific focus on the change in the social relations of production, ideology, and institutions from a neo-Gramscian theoretical framework that allows considering the special relationship between the state and civil society as well as the economic and political.